An in-vitro study to compare the force degradation of pigmented and non-pigmented elastomeric chains - Palathottungal Joseph Antony; Joby Paulose (Wolters Kluwer Medknow Publications, 2014)
Aim: The purpose of the study was to compare the force delivery and force decay property of pigmented and non-pigmented elastomeric chains, widely used in orthodontic practice. Materials and Methods: Force delivered by the samples consisting of pigmented and non-pigmented elastomeric chains obtained from 3 manufacturers were tested at 3 time intervals (as received, after 24 hours and 21 days of stretching) to measure the force delivered by the test samples, as well as the force decay over time. Results: The force delivered by the non-pigmented samples was significantly greater than the pigmented ones at all 3 time intervals irrespective of the brand. Force decay was more significant in case of pigmented samples. Force decay was greater noticed in first 24 hours of testing and a gradual decrease in force was observed from 24 hours to 21 days in all test samples irrespective of the brand or color. Conclusion: Non-pigmented elastomeric chains exhibited better force delivery and less force decay percentage when compared to pigmented chains. Though colored elastomeric chains are widely used in present day orthodontic practice to satisfy the younger age group patients, the study ascertains the prudential use of pigmented and non-pigmented chains for efficient and faster orthodontic treatment.